Support Development and Intermodal Transportation at Station to Help Reactivate The Cibatu-Garut Railroad - rita rita; elvyana simbolon; anak Agung Bagus Randitya (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2020)
The implementation of sustainable transport systems has become a requirement in the policy and management strategies in handling the problems of not fully integrated transportation infrastructure network, transprotation service network and the level of public transport service in the development of a transportation network. As today, reactivation of the Railway line from Cibatu-Garut is being carried out, with the length of the Cibatu-Garut railway line being around 19.2 km. Some of the old stations used include Garut Station, Wanaraja Station and Pasir Jengkol.Station. From the results of data collection that has been carried out, it is necessary to increase the role of other public transportation as advanced transportation and increase accessibility and integration of public transport services at the transportation node (train station) by developing advanced transportation services and good modal transfer facilities. So that a sustainable transportation system will be done.